Organization of SNAREs within the Golgi Stack - Malsam, Jörg; Söllner, Thomas (Cold Spring Harbor perspectives in biology, 2011)
Antero- and retrograde cargo transport through the Golgi requires a series of membrane fusion events. Fusion occurs at the cis- and trans-side and along the rims of the Golgi stack. Four functional SNARE complexes have been identified mediating lipid bilayer merger in the Golgi. Their function is tightly controlled by a series of reactions involving vesicle tethering and SM proteins. This network of protein interactions spatially and temporally determines the specificity of transport vesicle targeting and fusion within the Golgi.